2021
DOI: 10.1002/hep.31293
|View full text |Cite
|
Sign up to set email alerts
|

PLAGL2‐EGFR‐HIF‐1/2α Signaling Loop Promotes HCC Progression and Erlotinib Insensitivity

Abstract: Background and Aims Hepatocellular carcinoma (HCC) is the third leading cause of cancer‐related deaths worldwide, hence a major public health threat. Pleomorphic adenoma gene like‐2 (PLAGL2) has been reported to play a role in tumorigenesis. However, its precise function in HCC remains poorly understood. Approach and Results In this study, we demonstrated that PLAGL2 was up‐regulated in HCC compared with that of adjacent nontumorous tissues and also correlated with overall survival times. We further showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…This is similar to our Kaplan-Meier survival analysis of the HCC gene dataset from TCGA. Moreover, increasing evidences speculate a positive regulatory role for HIF-2α in brosis, pathogenesis, metastasis, and resistance to anti-tumor treatments in HCC (22,(39)(40)(41)(42)(43)(44). Taken together, HIF-2α may be a potential target for the treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to our Kaplan-Meier survival analysis of the HCC gene dataset from TCGA. Moreover, increasing evidences speculate a positive regulatory role for HIF-2α in brosis, pathogenesis, metastasis, and resistance to anti-tumor treatments in HCC (22,(39)(40)(41)(42)(43)(44). Taken together, HIF-2α may be a potential target for the treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is an important feature of the microenvironment of solid tumors, and promotes malignancy. [32][33][34][35][36]44 In several previous studies microRNAs have reportedly mediated the cancer-promoting effects of hypoxia in various tumor types. 54 Zheng et al 41 suggested that hypoxia could drive tumorigenesis and metastasis in HCC by downregulating miR-196-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a main feature of HCC, and strong evidence suggests that it may promote HCC progression by regulating characteristics associated with malignancy, including cancer stem-like properties, 32 proliferation, 33,34 metastasis, 35,36 and epithelial-mesenchymal transition 37,38 in both hypoxia-inducible factor 1-alpha (HIF1-α)-dependent and HIF1-α-independent manners. Dou et al 39 reported that hypoxia contributed to growth and metastasis by increasing the expression of tuftelin 1, which is an HCC oncoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…PLAGL2 also enhances Wnt6 expression at the transcriptional level and promotes the progression of colorectal cancer 9 . In addition, the PLAGL2-EGFR-HIF-1/2α signalling loop induces the malignant phenotype of liver cancer and the chemotherapy resistance of erlotinib 10 . Although growing evidence has showed that PLAGL2 functions as a dominant oncogene in gastrointestinal cancers 7 , 11 , 12 , the exact role of PLAGL2 and the underlying mechanism in GC remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%